IInovasi Teknologi Sebagai Pendukung Keberhasilan Usaha - Maria Fransiska Ema Koten; Sofia Metilda Oldin; Mesly Olivia Liu; Elisabeth Apriana Poso; Yosep B. N. A. Koten; Sedelis Nenabu; Enike Tje Yustin Dima (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study aims to analyze the role of technological innovation in supporting business success in the context of increasingly competitive and dynamic business development. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation studies to obtain a comprehensive understanding of technology implementation in business activities. The results indicate that technological innovation plays a significant role in improving operational efficiency, accelerating work processes, reducing production and administrative costs, expanding market reach, and encouraging the creation of more innovative products and services. The use of digital platforms, information systems, and online marketing strategies also helps businesses adapt to changes in consumer behavior and strengthen their competitiveness. However, the implementation of technology still faces several challenges, including limited human resources, low digital literacy, inadequate infrastructure, and limited capital for technology investment. Therefore, appropriate managerial strategies, continuous training, and the improvement of digital competencies are required to optimize the use of technology, particularly for small and medium enterprises facing rapid digital transformation today. This study concludes that technological innovation is an essential factor in supporting sustainable business success.